Self-Regulation Learning Relations and Student Perception to Social Support of Parents with Learning Motivation - Neni Sriwahyuni; Syahniar; Riska Ahmad (Fakultas Ilmu Pendidikan UNP)
This research is done due to students’ low learning motivation. Self- regulated and student perception regarding parents’ social support are factors suspected influence students learning motivation. This research aims at describing and testing: (1) self-regulated learning, the student’ perception about their parents’ social support and learning motivation, (2) the correlation of self-regulated learning and their perception saperately toward the students’ learning motivation, and (3) the correalation of the students’ self-regulated learning and perception together toward their learning motivation. This research applied the correlational descriptive type of the quantitative method. The population of this research were 996 students of Senior High School 1 Sutera Pesisir Selatan. The sample were 283 students that were chosen by using proportional random sampling tecnique. The instrument of the research was the Likert scala model. were analysed by using the descriptive statistics as well as simple and multiple regressions. This discover reseach show: that the students’ self-regulated leaning was in the “good” category while their perception about their parents’ social supports was in the “positive” category and their learning motivation was in the “high” category. Second, there was a correlation of self-regulated learning and their perception separately toward the students’ learning motivation. Third, there was a correlation of the students’ self-regulated learning and perception together toward their learning motivation. Those result can be implied as a student-need analysis to design the guidance and counseling service program at the school.